Immune Responses Against SARS-CoV-2 WT and Delta Variant in Elderly BNT162b2 Vaccinees - Jäger, Michael; Sonnleitner, Sissy Therese; Dichtl, Stefanie; Lafon, Eliott; Diem, Gabriel; Walder, Gernot; Lass-Flörl, Cornelia; Wilflingseder, Doris; Posch, Wilfried (Frontiers in Immunology, 2022)
Background: Residents of nursing homes are one of the most vulnerable groups during the severe acute syndrome coronavirus 2 (SARS-CoV-2) pandemic. The aim of this study was to characterize cellular and humoral immune responses in >70 years old participants before vaccination, after first and second vaccination with BNT162b2 in contrast to second dose-vaccinated participants younger than 60 years. Methods: Peripheral blood mononuclear cells of 45 elderly and 40 younger vaccinees were analyzed by IFN ELISpot, specific immunoglobulin G antibody titers against SARS-CoV-2 spike protein and neutralization abilities against SARS-CoV-2 wild-type (WT) and Delta variant (B.1.617.2). Results: Our results clearly demonstrate a significantly increased T cell response, IgG titers and neutralization activities against SARS-CoV-2 WT and Delta between first and second vaccination with BNT162b2 in elderly vaccinees, thereby highlighting the importance of the second booster. Interestingly, similar cellular and humoral immune response against SARS-CoV-2 WT and Delta were found after the second vaccine dose in the young and the elderly group. Conclusions: Our data demonstrate a full picture of cellular and humoral immune responses of BNT162b2-vaccinees in two age cohorts. In all vaccinees SARS-CoV-2 WT-specific antibodies with similar neutralizing activity were detected. After the second vaccination, neutralization titers against SARS-CoV-2 Delta were impaired in both age groups compared to SARS-CoV-2 WT, thereby emphasizing the need for an additional booster to overcome raising variants of SARS-CoV-2.